Fractal study on fracture surface of PAN-based carbon fiber. Issue 181 (13th June 2017) - Liu, Shuiping; Lu, Shuang
ABSTRACT: PAN-based carbon fiber is a type of brittle material whose fracture surface has a structure peculiar to brittle materials. The tensile strength of a carbon fiber is determined by the strength of weak links in the fiber to a large extent. Since fracture surface is a type of weak link, the fracture surfaces of PAN-based carbon fibers were investigated in this article. SEM (Scanning Electron Microscopy) micrographs of selected carbon fibers with different tensile strengths were analyzed on computer and the fractal dimensions of fracture surfaces were obtained on the basis of fractal theories. The relationship between the tensile strength of PAN-based carbon fiber and the fractal dimension of its fracture surface was demonstrated.